Synthesis and Characterization of Pyrazine Derived Compounds as Potential Materials for Hole Transporting Layer (HTL) - Vety Sri Harlinda Ayudha; Mokhamat Ariefin (Jurnal Kimia Sains dan Aplikasi, 2020)
Three simple compounds that have the potential as a hole transporting layer (HTL) based on pyrazine derivatives conjugated with electron donor groups in the form of triphenylamine have been successfully synthesized and characterized. The synthesis began with a substitution reaction at high temperatures between 4-bromoaniline and 4-iodoanisole to produce 4-bromo-N,N-bis(methoxyphenyl)-aniline, followed by substitution of bromo atoms with tributylstanum at low temperatures and inert atmosphere (N2) producing 4-methoxy-N-(4-(tributylstanyl)phenyl)aniline. The conjugation reaction was carried out through a Stille coupling reaction between 1,2-bis (4-bromophenyl)ethane-1,2-dione with 4-methoxy-N-(4-(tributylstanyl)phenyl) aniline at high temperatures with the aid of a Pd(PPh3)4 catalyst in an inert atmosphere (N2). The reaction was continued with the imination reaction with 3 compounds, i.e., 1,2-diaminobenzene, 3,3-diaminobenzidine and 2,3-diaminopiridin to produce three HTL compounds that were namely 4’,4”-(quinoxaline-2,3-diyl)bis (N,N-bis(4(methoxyphenyl)-[1,1’-biphenyl]-4-amine) (DNB), 4’,4’’’,4’’’’’,4’’’’’’’-([6,6’-biquinoxaline]-2,2’,3,3’-tetrayl) tetrakis(N,N-bis(4-methoxyphenyl)- [1,1’-biphenyl] -4-amine) (bDNB), and 4’,4’’’-(pyrido[2,3-b]pyrazine-2,3-diyl)bis(N,N-bis (4-methoxyphenyl)-[1,1’-biphenyl]-4-amine) (DNP). The optical and electrochemical properties of DNB, bDNB, and DNP were analyzed by UV-Vis and Differential Pulse Voltammetry (DPV). The optical and electrochemical properties show the energy levels of the HOMO and LUMO of the three compounds. Hence their potential can be estimated as HTL compounds. The three compounds show λmax of 348 nm, 356 nm, and 350 nm for DNB, bDNB, and DNP. Based on DPV results, the HOMO values for DNB, bDNB, and DNP are -5.03 eV, -5.02 eV, and -4.98 eV and LUMO values of -2.46 eV, -2.76 eV and -2.87 eV, respectively. The three compounds' thermal properties were analyzed using TGA, with the results showing that the three compounds had good thermal resistance with a decomposition point above 400°C. Based on optical, electrochemical, and thermal analysis, DNB and bDNB have almost the same properties. Thus, it is expected that the three compounds have the potential as HTL material, with DNB and bDNB better than DNP.